Influence of jasmonic acid on the growth and antimicrobial and antioxidant activities of Lavandula angustifolia Mill. propagated in vitro - Andrys Dominika (Folia Horticulturae, 2018)
The aim of the study was to determine the influence of jasmonic acid added to culture medium on the growth of plants and antioxidant properties of dry plant material, as well as on the antimicrobial properties of essential oils produced by the narrow-leaved lavender. For plant propagation, MS media supplemented with JA at concentrations of 0.2-1.5 mg dm−3 were used. The use of the lower JA concentrations did not influenced the growth parameters measured, whereas at the higher concentrations (1 and 1.5 mg dm−3) JA caused growth inhibition and a decrease in plant weight. With increasing JA concentration, the number of secretory trichomes decreased. Addition of 0.5 mg dm−3 JA caused an increase in secretory trichome diameter on both the adaxial and abaxial surface of leaves (83.3 and 73.2 μm, respectively). The antioxidant activity of the lavender plants propagated on media with the addition of JA (regardless of the concentration used) was higher than that of the control plants. The plants from JA-supplemented media were used to isolate essential oils, the antimicrobial activity of which was tested using the disc diffusion method at the concentrations of 10 and 50%. All the oils tested exhibited activity towards Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Staphylococcus epidermidis and Candida albicans. The essential oils isolated from the plants propagated on the medium with 1 mg dm−3 JA were characterized by the highest antimicrobial activity against the majority of the tested microorganisms.